2016
DOI: 10.1111/jmwh.12376
|View full text |Cite
|
Sign up to set email alerts
|

The Baby‐Friendly Hospital Initiative as an Intervention to Improve Breastfeeding Rates: A Review of the Literature

Abstract: Many of the studies regarding the effectiveness of the BFHI have been hampered by weak designs or methodologic limitations. Research conducted in the United States and employing experimental designs would help to more conclusively determine the effectiveness of the BFHI as an intervention to improve breastfeeding rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 31 publications
0
55
1
Order By: Relevance
“…Of note, however, is that an increase in exclusive breastfeeding in the hospital is a criterion for Baby‐friendly certification. Thus, concluding that the intervention increases breastfeeding initiation employs a circular logic because the intervention itself cannot also be a measured outcome” (Howe‐Heyman & Lutenbacher, , p.100).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, however, is that an increase in exclusive breastfeeding in the hospital is a criterion for Baby‐friendly certification. Thus, concluding that the intervention increases breastfeeding initiation employs a circular logic because the intervention itself cannot also be a measured outcome” (Howe‐Heyman & Lutenbacher, , p.100).…”
Section: Discussionmentioning
confidence: 99%
“…On this regard, some countries like the United Kingdom or France do not use the international 75% criterion for accreditation (Malik & Cutting, ) to avoid a self‐selection effect. Scepticism towards the methodologies used to assess the impact of BFHI policies have increased over the years (Atchan et al, ; Bartington, Griffiths, Tate,, & Dezateux, ; Howe‐Heyman & Lutenbacher, ; Merewood et al, ; Munn, Newman, Mueller, Phillips, & Taylor, ; Patnode, Henninger, Senger, Perdue, & Whitlock, ) and with that, the impact of BFHI has been increasingly questioned (Brodribb et al, ; Gomez‐Pomar & Blubaugh, ; Howe‐Heyman & Lutenbacher, ). Prospective studies are needed to examine causal factors associated with increased or decreased BF rates within baby‐friendly hospitals (Merewood et al, ; Munn et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Many countries have implemented the BFHI and found a dramatic increase in breastfeeding rates among their population . The Agency for Healthcare Research and Quality conducted a systematic review of 9 cohort studies related to breastfeeding (1,227,532 women) and concluded that rates of breastfeeding are higher among women who give birth in BFHI‐certified facilities compared with non‐BFHI facilities .…”
Section: The 10 Steps To Successful Breastfeedingmentioning
confidence: 99%
“…Study participants were recruited while being admitted to the post-natal maternity units of the 12 de Octubre Hospital, a metropolitan certified Baby-Friendly Hospital [27] in Madrid, Spain. This is the hospital to which most of the Chinese population in Madrid is referred (being the nearest hospital to the largest concentration of Chinese population in Spain) [28].…”
Section: Aimmentioning
confidence: 99%